An assessment of the protected Gilbert Bay cod population and evaluation of factors driving observed changes in abundance - Nguyen, Khanh Q.; Morris, Corey J.; Green, John M.; Pennell, Curtis; Hanlon, Jacqueline M. (Frontiers in Ocean Sustainability, 2025)
The Gilbert Bay Marine Protected Area (MPA), Labrador, was created in 2005 to conserve a coastal resident population of Atlantic cod (Gadus morhua). Scientific research and monitoring have been conducted consistently since 1998, and data have been used to assess the health of the Gilbert Bay cod population and provide management advice. This study has two parts: the first part applies a standard quantitative fisheries stock assessment methodology (length-based stock assessment) to provide growth and mortality parameters; and the second part considers all available MPA indicator monitoring data to evaluate which factors contribute most importantly to observed long-term population trends using Bayesian Model Averaging. Model results indicated that Gilbert Bay cod exhibit low growth rates and low natural mortality. It estimated that the protected population decreased from 39,000 to 9,000 individuals from 1998 to 2019. Those remaining individuals are mostly sexually immature and <35 cm total length (TL). In the second part of the study, monitoring data, including environmental metrics, annual abundances of cod eggs, pelagic juveniles, demersal juveniles (ages 1–4 years.), adults, and fishery removals, are used to assess which factors contributed most importantly to the observed population trends over time. Commercial cod landings adjacent the MPA boundaries explained 89.2% of the variability in cod egg density and 100% of the changes in adult fish abundance. Environmental conditions had a negligible role in cod population decline. Despite changes in fish community structure within Gilbert Bay, a reduction in fishing mortality on mature Gilbert Bay cod could enable the survival of strong year classes and promote recovery of the Gilbert Bay cod population.